Students' Consumerism Attitude to Higher Education Institutions - Raden Johnny Hadi Raharjo; G. Oka Warmana; Damar Kristanto; Anandya Zalva Yunnafisah; Andrew Baihaqi Firdaus (Nusantara Science and Technology Proceedings, 2022)
Modern society argues that society depends on the ideology of consumption. Consumption is not only a marker of the social status of a person or group. Status consumption is a mechanism used by consumers to gain social status or prestige by buying and consuming goods that customers and their significant other consider high status. but also a way of solving problems, constructing meaning for the environment around us, and even forming personal identities. The increasing reach of the ideology of consumerism has expanded the traditional definition of what is called a "commodity" to an intangible service. When service becomes a commodity, the institutions that provide it tend to focus more on activities that are consumer service, with the aim of attracting and retaining customers who are influenced by market ideology. This model has been used by higher education institutions, namely universities, so that consumerism occurs by students who need educational service products, therefore this study wants to know the consumerism behavior of students. This study uses a quantitative approach, with a sample of 500 respondents. The survey shows that students tend to act as consumers in the education provided by the university. Consumerism is correlated with expectations of lecturers, job preparation, and grades, but not with student responsibilities.